2017
DOI: 10.1021/acs.nanolett.7b00132
|View full text |Cite
|
Sign up to set email alerts
|

A Liposome Encapsulated Ruthenium Polypyridine Complex as a Theranostic Platform for Triple-Negative Breast Cancer

Abstract: Ruthenium coordination complexes have the potential to serve as novel theranostic agents for cancer. However, a major limitation in their clinical implementation is effective tumor accumulation. In this study, we have developed a liposome-based theranostic nanodelivery system for [Ru(phen)2dppz](ClO4)2 (Lipo-Ru). This ruthenium polypyridine complex emits a strong fluorescent signal when incorporated in the hydrophobic lipid bilayer of the delivery vehicle or in the DNA helix, enabling visualization of the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 51 publications
(95 reference statements)
1
76
1
Order By: Relevance
“…The application of nanostructures improves the delivery and penetration of Ru(II) complexes, 336,337 thus increasing the concentration in cells. For example, the combination of nanomedicine and Ru(II) complexes yields significant anticancer efficacy in drug resistant cancer cells as they are not substrates for MDR transporters.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The application of nanostructures improves the delivery and penetration of Ru(II) complexes, 336,337 thus increasing the concentration in cells. For example, the combination of nanomedicine and Ru(II) complexes yields significant anticancer efficacy in drug resistant cancer cells as they are not substrates for MDR transporters.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The liposomal formulations of Ru have also been proposed [51,52] Shen et al demonstrated encapsulation of ruthenium polypirydine complex [Ru(phen) 2 dppz](ClO 4 ) 2 in a liposome carrier (Lipo-Ru), composed of dipalmitoylphosphatidylcholine (DPPC), cholesterol, and distearoylphosphatidylethanolamine (DSPE)-PEG (polyethylene glycol). The schematic of the Lipo-Ru is presented in Figure 2A.…”
Section: Liposomesmentioning
confidence: 99%
“…In this way, NPMBC seem to have good in vivo pharmacokinetic properties. They are absorbed quickly into plasma [16,39,44,52], the circulation time in the bloodstream is long [42], their uptake in the tumor tissue is significant [16,28,32,37,39,41,42,44,46,51,52,60,70], their accumulation in organs (brain, liver, kidney, spleen, heart, lung, and intestine) is low [16,28,39,41,42,44,51,52,55] and the clearing rate is good [51].…”
Section: Anticancer Effects Of Non-platinum Mbc (Npmbc)mentioning
confidence: 99%
“…Furthermore, due to the lack of specific molecular targets in this subtype of BC [7], which makes its treatment difficult, chemotherapy remains an essential component for the management of TNBC, both adjuvant and neoadjuvant therapy [8,9]. Besides their diagnostic use [14][15][16][17][18][19][20][21], metallodrugs or metal-based complexes (MBC) stand out for being promising chemotherapeutic agents [22]. The therapeutic potential of MBC has long been known; however, their role in the treatment of cancer is relatively recent (1960s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation